Diversity and antibiotic resistance of Acinetobacter spp. in water from the source to the tap - Narciso-da-Rocha, Carlos (2018)
Acinetobacterspp. are ubiquitous bacteria in the environment.Acinetobacterspp. isolated from a municipal drinking water treatment plant and from connected tap waterwere identified to the species level on the basis ofrpoB genepartial sequence analysis. Intraspecies variation wasassessed based on the analysis of partial sequences of house-keeping genes (rpoB,gyrB, andrecA). Antibiotic resistancewas characterized using the disk diffusion method and iso-lates were classified as wild or non-wild type (non-WT),according to the observed phenotype. The strains ofAcinetobacterspp. were related to 11 different validly pub-lished species, although three groups of isolates, presentinglowrpoB sequence similarities with previously describedspecies, may represent new species. Most of the isolateswere related to the speciesA. johnsoniiandA. lwoffii.These two groups, as well as others related to the speciesA. parvusandA. tjernbergiae, were detected in the watertreatment plant and in tap water. Other strains, related to thespeciesA. pittiiandA. beijerinckii, were isolated only fromtap water. Most of the isolates (80 %) demonstrated wild type (WT) to all of the 12 antibiotics tested. Non-WT fortetracycline, meropenem, and ceftazidime, among others,were observed in water treatment plant or in tap watersamples. Although, in general, this study suggests a lowprevalence of acquired antibiotic resistance in waterAcinetobacterspp., the potential of some species to acquireand disseminate resistance via drinking water is suggested.